Framing Pemberitaan Pembangunan dan Pengembangan Pelabuhan Penyeberangan Amolengo-Labuan Di Media Online - Satyadharma, Maudhy (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2023)
The government is very aware of the presence of the Amolengo-Labuan Ferry Port in connecting the mainland and islands in Southeast Sulawesi Province so that it needs development to become a Modern Port. This research was conducted to analyze news framing related to the development of the Amolengo-Labuan Ferry Port during 2022. The results of the study concluded that online media has carried out its function as a medium for providing information to the public regarding the plan to develop the Amolengo-Labuan Ferry Port to become a modern port which will be implemented by the Provincial Transportation Service It is hoped that Southeast Sulawesi will not only be able to connect the mainland and islands in the Province of Southeast Sulawesi but also be able to encourage increased connectivity between regions, increase the mobility of people and goods and encourage economic development in the Province of Southeast Sulawesi.